Dietary Prebiotics, Milk Fat Globule Membrane, and Lactoferrin Affects Structural Neurodevelopment in the Young Piglet - Mudd, Austin T.; Alexander, Lindsey S.; Berding, Kirsten; Waworuntu, Rosaline V.; Berg, Brian M.; Donovan, Sharon M.; Dilger, Ryan N. (Frontiers in Pediatrics, 2016)
Introduction: Milk fat globule membrane (MFGM) and lactoferrin have been identified as two components that have potential to affect neurodevelopment. While concentrations of some MFGM constituents in infant formulas are within human milk range, they may not be present at optimal or clinically effective levels. However, lactoferrin levels of infant formulas are consistently reported to be lower than human milk. This study sought to provide a novel combination of prebiotics, bovine-derived milk fat globule membrane and lactoferrin and assess their influence on neurodevelopment. Methods: Twenty-four male piglets were provided either TEST (n=12) or CONT (n=12) diet from 2 to 31 d of age. Piglets underwent spatial T-maze assessment starting at 17 d of age, were subjected to magnetic resonance imaging at 30 d of age, and were euthanized for tissue collection at 31 d of age. Results: Diffusion tensor imaging revealed differences in radial (P = 0.032) and mean (P = 0.028) diffusivities in the internal capsule, where CONT piglets had higher rates of diffusion compared with TEST piglets. Voxel-based morphometry indicated larger (P < 0.05) differences in cortical grey and white matter concentrations, with CONT piglets having larger tissue clusters in these regions compared with TEST piglets. In the spatial T-maze assessment, CONT piglets exhibited shorter latency to choice compared with TEST piglets on d 2 of acquisition and d 3 and 4 of reversal. Conclusion: Observed differences in microstructure maturation of the internal capsule and cortical tissue concentrations suggest that piglets provided TEST diet were more advanced developmentally than piglets provided CONT diet. Therefore, supplementation of infant formula with prebiotics, milk fat globule membrane and lactoferrin may support neurodevelopment in human infants.